Tutor Empowerment in the Non-Formal Education Ecosystem: A Digital Multimodal Based Entrepreneurship Development Model for Economic Independence in the Era of Disruption - Imam Shofwan; Fakhruddin Shofwan; Hendra Dedi Kriswanto; All Fine Loretha (Edukasi, 2025)
In the midst of the structural challenges of Indonesia's job market and digital disruption, non-formal education (PNF) plays a crucial role in equipping the community with relevant skills. This article analyzes a tutor empowerment model as a strategic effort to develop digital multimodal based entrepreneurship education in the PNF program in Ungaran Regency. Using a qualitative case study approach, this study examines the process and impact of training programs designed to improve the digital and pedagogical competencies of tutors. Data was collected through in-depth interviews, participatory observations, and document analysis, then analyzed thematically. The results show that this empowerment program significantly transforms the role of tutors from conventional teachers to digital learning architects who are able to design interactive learning experiences. The implementation of multimodal pedagogy has been proven to increase student engagement and learning motivation, as well as facilitate the development of early-stage digital entrepreneurship skills. This study concludes that tutor empowerment is a critical-path factor for the success and relevance of PNF in the digital era. However, the sustainability of these innovations is highly dependent on the existence of systemic support and affirmative policies to address the professional precariats that educators in the non-formal pathway have been facing.